DIAGNOSTICS OF ONLINE LEARNING DIFFICULTIES IN SCIENCE SUBJECT AND EFFORT TO OVERCOME IN ELEMENTARY SCHOOL-AGED CHILDREN IN THE BRIMOB OF SERANG CITY - Edwinia, Ristin; Suratno, Tatang; Wuryastuti, Sri (Didaktika, 2021)
Learning science is often considered difficult by students because the way of teaching it tends to be rote, not discovery. Especially in a pandemic situation like this that demands independent learning due to social restrictions. For this reason, educators need to have the ability to understand students' learning experiences and reflect on them as an effort to diagnose learning difficulties or obstacles. Related to that, this research applies narrative inquiry (narrative research). In narrative research, the researcher attempts to describe the life situations of several individual students and reflect on these experiences as diagnostic of their learning difficulties. Researchers made observations, made field notes and conducted interviews. The collected data is then analyzed and presented in a narrative manner by taking into account the situational interactions that are revealed in it. Based on the data analysis, the researcher found several things that influenced the students' learning difficulties. In general, there are several diagnostic causative factors that come from within students, including: 1) emotional mental condition; 2) reactive way of thinking; 3) lack of awareness; and 4) low interest in learning. Meanwhile, several factors from outside the students include: 1) lack of parental attention; 2) inconducive home atmosphere; 3) unsupportive environmental conditions; 4) social media influence; 5) unattractive and monotonous teaching methods; as well as 6) incomplete learning facilities. Efforts to overcome learning difficulties need to pay attention to these two aspects. Educators need to have the ability to understand students' learning experiences and design learning strategies that suit their characteristics. Apart from that, the role of parents and environmental conditions must also be considered in order to create conducive learning conditions.